Science and Indigenous knowledge in resource management in the Canadian Arctic - Wandel, J; Smit, B; Pearce, T; Ford, J (Routledge, 2011)
As progress towards a greater knowledge in sustainability science continues, the question of how better to integrate scientific progress with actual decisions made by practitioners remains paramount. This book aims to help close the gap between science and practice. Based on a two year collaborative project between Harvard and Clark Universities, the book takes as its focus the vulnerability and resilience of people around the world to the effects of environmental change, a mature area of research in which one might expect the gap between science and policy/practice to have been extensively bridged. Integrating Science and Policy presents analysis of past studies, interviews conducted with the producers and users of scientific knowledge, and case studies performed by leading scholars across a spectrum of international settings and political systems. Crucially, the authors identify new directions and tools for closing the gap between science and policy across a range of situations and societies. The result is an illuminating collection of studies and analyses that suggest to researchers, students, practitioners, and policy-makers alike how best to ensure that high quality environmental research informs good environmental policy and practice. [Book Synopsis].